Long-term power systems integration using OSeMOSYS SAMBA - South America Model Base - and the bargaining power of countries : a cooperative games approach - Moura, Gustavo Nikolaus Pinto de (2017)
This study intends to contribute to a better understanding of both advantages and drawbacks of power systems interconnection processes in South America. Based on data available in national and international reports, scenarios for the power supply sector expansion were modelled in the Open Source energy Modelling System – OSeMOSYS – using a new framework named South America Model Base – SAMBA. Features related to costs, carbon emissions, hydro reservoirs, technological performance, electricity demand, population growth, time zones and reserve margin were considered. The Brazilian and Bolivian perspectives of power systems integration were modelled according to data presented by national power plans. The comparison of different scenarios provides insights regarding the contribution of renewable energy generation and sheds light on cross-border trade perspectives in South America. Additionally, using a cooperative games approach, the bargaining power of each country (player) was calculated by applying the Shapley value concept. The proposed methodology may provide important information to support policy makers in international negotiations, thus considerably reducing incentives to non-cooperative actions.